Dynamic ecological model of human development of the school desertion in Aymares Apurimac - Espinoza, Grace (2015)
The present article reports of a qualitative study in the school desertion in Aymaraes Apurimac. The aim of the study was to characterize the factors involved in the school desertion, by means of an ecological model of human development of Urie Bronfenbrenner. The different factors brought as reasons of the school desertion, are organized, in agreement type of environment that they constitute for the student who deserts. Macrosystem, exosystem, mesosystem and microsystem. The latter system organizes, the psychological aspects of the students, and is explained across the theory of the Personal development of Pedro Ortiz. The results realize of the positive or negative interaction, of each of the factors that involved in the problematics for themselves, do not determine the problem: the interaction of every each one of these factors is analized by means of the dynamics of the systems. Of each of the factors of a system is that it emerges the school desertion.